2022
DOI: 10.3389/fmicb.2022.891902
|View full text |Cite
|
Sign up to set email alerts
|

IS6110 Copy Number in Multi-Host Mycobacterium bovis Strains Circulating in Bovine Tuberculosis Endemic French Regions

Abstract: IS6110 is an insertion sequence found in the Mycobacterium tuberculosis complex, to which Mycobacterium bovis belongs, which can play a role in genome plasticity and in bacterial evolution. In this study, the abundance and location of IS6110 on M. bovis genomic data of French animal field strains were studied. A first analysis was performed on a panel of 81 strains that reflect the national M. bovis population’s genetic diversity. The results show that more than one-third of them are IS6110 multicopy and that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 58 publications
1
7
0
Order By: Relevance
“…The phylogenetic distribution of SNPs, shown in Figure 4 , discriminated M. bovis genomes into 10 clusters well resolved by at least 200 SNP. This population structure is congruent with previous studies [ 7 , 53 ]. Indeed, the heatmap clearly highlights lineages based on the absolute SNP distance between strains, which supports a very clear separation between the lineage La1.2 (clusters G+H+I) and lineage La1.8.2 (cluster A+B+C).…”
Section: Resultssupporting
confidence: 93%
See 3 more Smart Citations
“…The phylogenetic distribution of SNPs, shown in Figure 4 , discriminated M. bovis genomes into 10 clusters well resolved by at least 200 SNP. This population structure is congruent with previous studies [ 7 , 53 ]. Indeed, the heatmap clearly highlights lineages based on the absolute SNP distance between strains, which supports a very clear separation between the lineage La1.2 (clusters G+H+I) and lineage La1.8.2 (cluster A+B+C).…”
Section: Resultssupporting
confidence: 93%
“…Insertion sequence (IS) analyses showed that all genomes have in the same position one copy of IS 1561 and six copies of IS 1081 , of which one is truncated ( Table 1 ). According to our previous study [ 53 ], the number of IS 6110 is variable depending on the genotype. With 12 copies, Mb1855, which belongs to the Eu3 clonal complex, presents the highest IS 6110 (1355 bp) copy number, which is one of the main reasons for its large genome size.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Another study disclosed M. bovis lineages by applying pangenome analysis, and the results showed 3900 core genes and only 96 accessory genes. 48 Ceres and other scientists have proven that: (1) the accessory genome of M. bovis is noticeably smaller than previously believed, and this nding supports continuing clonal evolution and a closed pangenome with low gene content uctuation throughout outbreaks; (2) several genes have frameshi mutations, including glpK, which has recently been linked to antibiotic tolerance in M. tuberculosis; (3) indels are the primary cause of the minor gene content variation that develops over brief time periods among closely related sequences; (4) multiple genes have potentially reversible homopolymeric tract alterations, indicating that phase variation may be a common method of gene regulation in MTBC. 140…”
Section: Wgs Insights Into the Genetic Diversity Of M Bovismentioning
confidence: 99%